Collaborative capacity development to complement stroke rehabilitation in Africa - Louw, Quinette (Human Functioning, Technology and Health, 2020)
This scholarly book focuses on stroke in Africa. Stroke is a leading cause of disability among adults of all ages, contributing significantly to health care costs related to long term implications, particularly if rehabilitation is sub-optimal. Given the burden of stroke in Africa, there is a need for a book that focuses on functioning African stroke survivors and the implications for rehabilitation within the African context. In addition, there is a need to progress with contextualised, person-centred, evidence-based guidance for the rehabilitation of people with stroke in Africa, thereby enabling them to lead socially and economically meaningful lives. The research incorporated in the book used a range of primary and secondary methodological approaches (scoping reviews, systematic reviews, meta-analyses, descriptive studies, surveys, health economics, and clinical practice guideline methodology) to shed new insights into African-centred issues and strategies to optimise function post-stroke.